The impact of oil palm empty fruit bunch (OPEFB) fibre loading on low density polyethylene (LDPE) - Muhamad Norhafiz, Nordin (2017)
Nowadays natural fibres seem to be the importants materials which become abundant substitute for the nonrenewable and expensive synthetic fibre. Natural fibres such as coir, banana, sisal, jute, kenaf and oil palm has been used as filler in thermoplastic composite for application in consumer goods, automotive parts and civil structure. Oil Palm Empty Fruit Bunch (OPEFB) fibre is one of the natural fibres that have a potential as a good reinforcement in thermoplastic composite. The objective is to investigate effect of different composition of fibre loading and fibre treatment on the water absorption properties and mechanical properties of OPEFB reinforced Low Density Polyethylene (LDPE) composite. OPEFB fibre was prepared from the raw fruit bunch. The fibre then filtered and chemically treated by using Sodium Chlorite and Potassium hydroxide. Biocomposites were prepared using OPEFB fibre which is treated and untreated at different composition 10% and 30% fibre loading. The biocomposite were compounded using extruder machine prior to compression moulding via hot press machine to form a sheet. After that, samples were prepared for tensile test and water absorption testing. Scanning Electron Microscope (SEM) was used to investigate the surface area of the fibre after the chlorite treatment. Results from this research show that at 10% treated fibre loading the tensile strength is the highest at 22 MPa. Lowest tensile strength at 30% untreated fibre loading. As predicted, by increasing the OPEFB composition, has increased the water absorption capability. However, untreated fibre has higher water absorption capability compared to treated fibre. Finally, observation on the untreated OPEFB showed silica bodies on its surface and the silica bodies can affect the tensile strength. The study has showed that the optimum fibre loading for the best performance of the composite achieved was at 10% treated fibre.